الأنماط المزاجية لدى عينة من مرضى السكري من النوع الثاني دراسة ميدانية في محافظة اللاذقية - سليمون, ريم; صبيرة, فؤاد; علي, رانيه عادل (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يحاول هذا البحث التعرف إلى الأنماط المزاجية السائدة لدى عينة من مرضى السكري النوع الثاني في محافظة اللاذقية، وكذلك تعرف الفروق بين متوسطات استجابات مرضى السكري النوع الثاني على مقياس الأنماط المزاجية تُعزى لمتغيرات (الجنس، مكان الإقامة). ولتحقيق أهداف البحث استخدم الباحث المنهج الوصفي التحليلي، وتم تطبيق مقياس الأنماط المزاجية على عينة من مرضى السكري بلغت (350) مريضاً ومريضة للعام (2013 - 2014)، وتم التأكد من صدقه وثباته بتطبيقه على عينة شملت (50) مريضاً وقد بلغ معامل الثبات بطريقة ألفا كرونباخ (0.75)، وبلغ (0.869) باستخدام معادلة سبيرمان براون. وانتهى البحث إلى أن بعد (قوة عمليات الكف) هو البعد الأكثر انتشاراً بين مرضى السكري النوع الثاني يليه بعد (دينامية العمليات العصابية) وأخيراً بعد (قوة عمليات الاستثارة). ووجود فروق ذات دلالة إحصائية تبعاً لمتغير الجنس (ذكور، إناث) لصالح الإناث، وعدم وجود فروق ذات دلالة إحصائية تبعاً لمتغير مكان الإقامة (ريف، مدينة) في كل بعد من أبعاد الأنماط المزاجية لدى أفراد عينة البحث من مرضى السكري النوع الثاني. The research try to defined the Temperament Models of sample of diabetes type II In The City Of Lattakia, as well as to identify differences in the differences between the mean responses of patients with diabetes type II on a scale of Temperament Models to the variables (sex, place of residence). Use the search descriptive analytical method. Application a scale of Temperament Models on the sample included (350) male and female patients, for the year 2013/2014. Pilot sample consisted of (50) patients, Reliability was established by Cronbach – Alpha Reliability at lest (0.75), and (0.869) by Spearman-Brown. Results showed that the field of the power to cease operations was the most spreading between Diabetes patients, and came after the dynamic operations of Neurotic field, at last the force in the excitement field, there are statistically significant differences according to six in favor of female, there are no statistically significant differences according to place of residence.